Lower Systolic Blood Pressure in Normotensive Subjects is Related to Better Autonomic Recovery Following Exercise - de Oliveira, Letícia Santana [UNESP]; Fontes, Anne Michelli G. G. [UNESP]; Vitor, Ana Laura Ricci [UNESP]; Vanderlei, Franciele M. [UNESP]; Garner, David M.; Valenti, Vitor E. [UNESP] (Springer Nature, 2020)
Blood pressure (BP) is a cardiovascular parameter applied to detect cardiovascular risk. Recently, the pre-hypertension state has received greater consideration for prevention strategies. We evaluated autonomic and cardiorespiratory recovery following aerobic exercise in normotensive individuals with different systolic BP (SBP) values. We investigated 30 healthy men aged 18 to 30 years divided into groups according to systolic BP (SBP): G1 (n = 16), resting SBP <110 mmHg and G2 (n = 14), resting SBP between 120–110 mmHg. The groups endured 15 minutes seated at rest, followed by a submaximal aerobic exercise on a treadmill and then remaining seated for 60 minutes also at rest, during recovery from the exercise. Cardiorespiratory parameters and heart rate (HR) variability (HRV) (rMSSD, SD1, HF [ms2]) were evaluated before and during recovery from exercise. G2 displayed slower return of SBP, rMSSD and SD1 HRV indices during recovery from exercise compared to G1. In conclusion, normotensive subjects with higher resting SBP (110 to 120 mmHg) offered delayed autonomic recovery following moderate exercise. We suggest that this group may be less physiologically optimized leading to cardiac risks.